Blood neutrophil to lymphocyte ratio as a predictor in patients with advanced hepatocellular carcinoma treated with hepatic arterial infusion chemotherapy. Issue 9 (17th November 2014) - Terashima, Takeshi; Yamashita, Tatsuya; Iida, Noriho; Yamashita, Taro; Nakagawa, Hidetoshi; Arai, Kuniaki; Kitamura, Kazuya; Kagaya, Takashi; Sakai, Yoshio; Mizukoshi, Eishiro; Honda, Masao; Kaneko, Shuichi
<x xml:space="preserve">Abstract</x> Aim Inflammation plays a critical role in cancer. The aim of the present study was to investigate the impact of neutrophil to lymphocyte ratio (NLR) on patients with advanced hepatocellular carcinoma (HCC) treated with hepatic arterial infusion chemotherapy (HAIC). Methods We retrospectively evaluated 266 patients with advanced HCC treated with HAIC between March 2003 and December 2012. NLR was calculated from the differential leukocyte count by dividing the absolute neutrophil count by the absolute lymphocyte count. Results The cut‐off level of NLR was set as the median value of 2.87 among all patients in this study. The objective response rate in the patients with low NLR was 37.6%, which was significantly better than that of the patients with high NLR (21.1%; P < 0.01). Multivariate analysis revealed that low NLR remained associated with the response to HAIC (P = 0.024). Median progression‐free survival and median overall survival in patients with high NLR were 3.2 and 8.0 months, respectively, which were significantly shorter than that of the patients with low NLR (5.6 and 20.7 months; P < 0.01 and P < 0.01, respectively). High NLR was an independent unfavorable prognostic factor in multivariate analysis. The patient outcome was stratified more clearly by NLR calculated after HAIC added to calculations before HAIC. Serum platelet‐derived growth factor‐BB level was positively correlated with NLR. Conclusion Results suggest that NLR is a useful predictor in patients with advanced HCC treated with HAIC. These findings may be useful in determining treatment strategies or in designing clinical chemotherapy trials in future.